Estación intermodal del norte: Plan parcial borde permeable de servicios periféricos Usaquén Bogotá, Colombia (2017)
This paper contains a summary of the planning, design and development of an urban and architectural project for the periphery of the city of Bogotá, under parameters dictated by law 388 of 1997 for planning of territory in Colombia go to the figure ofthe partial plan as an instrument for intervention in the territory; This work follows the steps by which arose and design a masterplan for the tibabita industry in the locality of Usaquén, Bogotá.